STRENGTHENING THE POSITION OF INDIGENOUS PEOPLE IN THE MANAGEMENT OF THE FOREST BY SUBSQUENT OF THE CONSTITUTIONAL COURT DECISION OF REPUBLIK INDONESIA NO.35/PUU-X/2012 TO SUPPORT OF REDD+ INDONESIA - Mayastuti, Anti; Rianto, Agus; Atikasari, Diah Apriani (Yustisia, 2017)
The problems of disputes over land ownership of forest between the government (in this case is the state) and the community, has been occured tens of years ago, but the increase was higher along with just an era of reform. A possession of forest resources has been dominated by large employers with the strength of their capital, while the local community (in this case of indigenous people) who rely on forest resources for generations before this country stood, their fate was even more marginalized. In fact, the existence of indigenous people with local wisdom value, plays an important role in forest management, as recognized in Act No.41 of 1999 about Forestry. Inequality of distribution of forest resources this mastery was seen as a base for real social conflict happens in the life of the community law. Furthermore it was published constitutional court’s verdict of RI No.35/PUU-X/2012 to provid e access to justice for indigenous people over the mastery of the forest. This recognition is strengthened by the existence of a REDD + Program aims to reduce emissions from deforestation and forest degradation that requires the existence of a customary law society active participation through the empowerment of local wisdom values.